2020
DOI: 10.1029/2020gl089931
|View full text |Cite
|
Sign up to set email alerts
|

City‐Scale Dark Fiber DAS Measurements of Infrastructure Use During the COVID‐19 Pandemic

Abstract: Throughout the recent COVID‐19 pandemic, real‐time measurements about shifting use of roads, hospitals, grocery stores, and other public infrastructure became vital for government decision makers. Mobile phone locations are increasingly assimilated for this purpose, but an alternative, unexplored, natively anonymous, absolute method would be to use geophysical sensing to directly measure public infrastructure usage. In this paper, we demonstrate how fiber‐optic distributed acoustic sensing (DAS) connected to a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(69 citation statements)
references
References 33 publications
1
66
2
Order By: Relevance
“…The weekday noise level strongly re ected the effects of the state of emergency, but the Sunday noise level likely re ected the concern of the people about the COVID-19 as most people continued to avoid non-essential outings even after emergency was lifted. Compared to other countries [12][13][14][15]24 , our results showed a higher reduction for the higher frequency range noise as MeSO-net stations are located in schools and the noise related to school activities is dominant. At frequencies <20 Hz, the reduction in the noise levels was unclear compared to those for higher frequencies because the number of stations that showed a high correlation coe cient was limited.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…The weekday noise level strongly re ected the effects of the state of emergency, but the Sunday noise level likely re ected the concern of the people about the COVID-19 as most people continued to avoid non-essential outings even after emergency was lifted. Compared to other countries [12][13][14][15]24 , our results showed a higher reduction for the higher frequency range noise as MeSO-net stations are located in schools and the noise related to school activities is dominant. At frequencies <20 Hz, the reduction in the noise levels was unclear compared to those for higher frequencies because the number of stations that showed a high correlation coe cient was limited.…”
Section: Discussioncontrasting
confidence: 66%
“…In addition, we could monitor the movement of people in a local area by using high-frequency seismic noise. It is suggested to monitor social isolation and the number of vehicles using seismic noise 15,24 . Although the global positioning system (GPS) is one of the most accurate ways to monitor the movement of people, it has recently become di cult to use the data because of privacy issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vehicle-induced ground vibrations are generated by the pitch and axle hop modes of the vehicle coupling to the road. Although far-field vibration levels depend on vehicle speed, road unevenness, the vehicle itself, and soil characteristics, vibration frequencies attributed to axle hop modes depend on vehicle distance and velocity (Lombaert et al, 2000;Lombaert and Degrande, 2001).…”
Section: Correlation With Mobilitymentioning
confidence: 99%
“…Earlier observations have indicated that the seismic noise level decreases during long holidays such as Christmas and New Year (Okada and Obara 2000). Seismic noise level reduction corresponding to social activity reduction for COVID-19 management has been reported around the world (Lecocq et al 2020;Poli et al 2020;Xiao et al 2020;Lindsey et al 2020). Reduction in social activity is rare and hence, its occurrence owing to COVID-19 enabled seismologists to understand the characteristics of cultural noise.…”
Section: Introductionmentioning
confidence: 99%